Journal of Instrumentation - Sirunyan; Tumasyan; Adam; Ambrogi; Babaev physicist engineer-issledovatelskogo Polytechnic University, candidate of physical and mathematical Sciences; Okhotnikov physicist engineer of Tomsk Polytechnic University; Baydali specialist in the field of automation and electronics Associate Professor of Tomsk Polytechnic University, Candidate of technical sciences, vice-rector for research and innovations (2018)
The algorithm developed by the CMS Collaboration to reconstruct and identify ? leptons produced in proton-proton collisions at vs=7 and 8 TeV, via their decays to hadrons and a neutrino, has been significantly improved. The changes include a revised reconstruction of ?0 candidates, and improvements in multivariate discriminants to separate ? leptons from jets and electrons. The algorithm is extended to reconstruct ? leptons in highly Lorentz-boosted pair production, and in the high-level trigger. The performance of the algorithm is studied using proton-proton collisions recorded during 2016 at vs=13 TeV, corresponding to an integrated luminosity of 35.9 fb-1. The performance is evaluated in terms of the efficiency for a genuine ? lepton to pass the identification criteria and of the probabilities for jets, electrons, and muons to be misidentified as ? leptons. The results are found to be very close to those expected from Monte Carlo simulation.